MEMPERTAHANKAN TRADISI BERKARAKTER DALAM INOVASI - Mahrusillah, Mohamad (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
This paper seeks to discuss about the management of the Maslakul Huda Kajen Pati Central Java Pesantren in the formation of Mandiri Individuals. In the research conducted by the writer through the field research method it can be said that in terms of management, the Maslakul Huda pesantren has used good and measurable management starting from: the pesantren board management recruitment system which in fact is active santri, the organizing system, supervision, material and educational methods that lead to the formation of the pesantren management. independent human being.